International Conference on Social Development and Social Work Education: Catholic University of America, Washington, DC Muharram 15-19/July 13-19, 1992 (American Journal of Islam and Society, 1992)
The Twenty-Sixth Congress of the International Association ofSchools of Social Work (IASSW) and the Seventh International Conferenceof the Inter-University Consortium for International Social Development(IUCISD) was held during 13-19 July 1992, in Washington, DC.These biennial international conferences are held simultaneously in thesame location to encourage interested social work educators to participatein the activities of both conferences.IASSW represents the interests of almost two thousand schools of socialwork and training institutes worldwide. The theme of the 1992 conferencewas "Realities of Global Interdependence: Challenges to SocialWork Education." Papers presented spanned the wide range of interestsof social work educators, from practice theory formulations to curriculumdevelopment to indigenous case materials. They also dealt with many diversefields of social work practice, for example, from family and childwelfare to rural and urban community development. Papers also dealt withclinical practice interests, polity, planning, and social development issues.IUCISD is a younger multidisciplinary organization of social workeducators and other allied professionals with an interest in the broaderarea of international social development. The theme of the IUCISD 1992conference was “Strategies of Social Development for Improving the HumanCondition.” Papers presented covered diverse topics, including socialwelfare provisions in Eastern Europe and countries of the former SovietUnion, peace and development, sustainable agriculture, refugees, socialdevelopment skills, social development and indigenous populations, socialdevelopment and aging populations, social development and children, andmany others ...